Force Image Schema in “The Farmer and the Cheeses” English Folktale - Ahmed , Sanaa Yousif; Abdulla, Dr. Ismail Abdulrahman (Thi Qar Arts Journal, 2025)
This study aims at analyzing a British folktale which is “The Farmer and the Cheeses” according to one of the cognitive semantic theories which is image schema theory. Force image schema and its eight categories are adopted in the analysis of a folktale. The study is authentic in introducing a new vision and innovative terms related to FORCE image schemas and schematic figurative language as these schemas are applied on a narrative form. The study introduces how FORCE schemas help in conceptualizing meaning to see their effectivity in construing narrative experiences. Throughout this study, many authentic results are achieved. The most important ones are: Objects can be endowed with abilities to be what can be called MOMENTORS i.e., the moving object’s momentum quantity is larger than any obstacle to stop that object. Moreover, in relation to schematic figurative language, an inanimate object can have kinetic energy is activated by another force therefore, the cheeses MOMENTUM can be called QUASI-MOMENTUM.